Alteridade de Jonathan Edwards na prática missiológica junto aos índios moicanos durante os anos 1751 a 1758 nos limites da Nova Inglaterra - Lima, Sérgio Paulo de (2017)
This research aims to study the alterity in the missiological practice of the American congregation theologian and philosopher Jonathan Edwards with the Mohicans (Mohicans), Housatonics, Mohawks, Onohquaugas and Oneidas between 1751 and 1758 in Stockbridge on the border of New England. As strategy was adopted a historical research having as theoretical reference the set of his writings in the village and primary texts of other authors like Samuel Hopkins, a personal friend and historian that analyzed the subject in itself and its actions that distinguished it with a theoretician-practical in the eighteenth century. Such research highlights the influences, motivations, guiding principles of its ministry, and its applicability at a time of known political, social, and economic difficulties of the brand-new American Nation. The expected results of this investigation point to a small increase in the understanding of edwardian alterity in missiological practices as a legacy to be reprobated in later times. Among other aspects, it is expected that its concepts, actions and results contribute to a development, growth and success in the management of the current and future missiological process.